PERAN MEDIA CENTER PWNU DALAM DAKWAH DI MEDIA DIGITAL - Zakia Norma Yunita (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2022)
The The development of the media today has developed very quickly. It started with the emergence of print media, so many other media technology innovations have emerged. Competition that causes the development of communication and information technology also leads to social changes in society. The development of media technology also contributes to improving the standard of existing information and can be easily accessed by the public. The proselytizing media is also a force for a dai in carrying out his mission. A dai must understand the development of existing technology, so in the saying it is stated